2016
DOI: 10.1155/2016/4058656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Stem Cell Transplantation for Liver Diseases: Monitoring, Clinical Translation, and Theranostics

Abstract: Stem cell transplantation has been investigated to rescue experimental liver failure and is promising to offer an alternative therapy to liver transplantation for liver diseases treatment. Several clinical studies in this field have been carried out, but the therapeutic benefit of this treatment is still controversial. A major obstacle to developing stem cell therapies in clinic is being able to visualize the cells in vivo. Imaging modalities allow optimization of delivery, detecting cell survival and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…MRI has a high spatial and temporal resolution, no tissue penetrating limit, and no radiation, but the disadvantages include relatively low sensitivity and low contrast, requiring a high load of cells with a magnetic label and comparatively long imaging times, with the possibility of affecting cell viability or biological interaction with the contrast agent [43,[62][63][64]. In this review, three studies used HSC tracking analysis by MRI with different magnetic fields, in which the highest magnetic field (17.6 Teslas) provided longer follow-ups (14 days after transplantation) when using low nanoparticle concentrations and incubation times in the cell labeling process.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has a high spatial and temporal resolution, no tissue penetrating limit, and no radiation, but the disadvantages include relatively low sensitivity and low contrast, requiring a high load of cells with a magnetic label and comparatively long imaging times, with the possibility of affecting cell viability or biological interaction with the contrast agent [43,[62][63][64]. In this review, three studies used HSC tracking analysis by MRI with different magnetic fields, in which the highest magnetic field (17.6 Teslas) provided longer follow-ups (14 days after transplantation) when using low nanoparticle concentrations and incubation times in the cell labeling process.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recurrent challenge is the ability to quantify the number of cells being detected and to confirm that the signal detected is actually an engrafted hepatocyte and not uptake by kuppfer cells or macrophages after hepatocytes have been destroyed. Additional imaging modalities including Cherenkov illumination imaging (CLI), photoacoustic imaging (PAI), surface enhanced Raman imaging (SERI), and theranostic imaging represent further strategies for in vivo cell transplantation monitoring (107109). Very recently, the thyroidal sodium iodide symporter (NIS) gene was used to visualize transplanted hepatocytes.…”
Section: Improving Transplanted Hepatocyte Survival and Monitoringmentioning
confidence: 99%
“…For example, mouse bone marrow–derived endothelial progenitor cells have been labelled with ferucarbotran, and the in vitro protocol for labelling did not impair proliferative ability [ 14 ]. Choi et al labelled human MSCs with ultrasmall paramagnetic iron oxides (USPIO) and green fluorescence protein (GFP) and demonstrated that labelled MSCs transplanted into the portal veins of immunosuppressed, hepatic-damaged rat models caused signal loss in the liver of transplanted cells in the early period of transplantation [ 15 , 16 ]. Limitations with tracking iron-labelled cells arise from low specificity, due to other regions in the image with low signal, as the lung parenchyma, and from difficulties to in vivo quantification of the signal loss.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to iron cell tracking, fluorine-19 ( 19 F) MRI with perfluorocarbon nanoemulsions has been used for cell tracking [ 17 , 18 ]. Its advantage is that the level of background 19 F signal in host tissue is virtually absent [ 15 ]. The 19 F nucleus is particularly suitable for labelling as its relative MRI sensitivity is only 17% less than that of 1 H. Previous studies have demonstrated effective labelling of MSCs with Celsense ATM DM Red [ 19 ].…”
Section: Introductionmentioning
confidence: 99%